Penerapan Activity Based Costing Pada Tarif Jasa Rumah Sakit (Studi Pada RSUD Kabupaten Bantaeng) - Nurdjanna Fadjrin Uluputty; Dewita Dewita (Bata Ilyas Journal of Accounting, 2021)
The purpose of this research is to find out that the activity-based costing system has been implemented in RSUD Prof.Dr.H.M. Anwar Makkatutu, Bantaeng Regency. The data used is descriptive qualitative data analysis, namely data obtained from observations, document analysis, field notes on research subjects. The research results can be seen by using a system activity based on a cost system that is suitable for implementation because the calculation of the cost rate is carried out by tracing the resource-consuming activities of inpatient. Activities that consume resources in the care of RSUD Prof.Dr.H.M. Anwar Makkatutu, namely patient care activities, and patient service activities.